(untitled) (Research, Society and Development, 2020)
Hypertension is a chronic disease, with high incidence, low rate of effective control and related to major cardiovascular complications. Medicinal plants can be an inexpensive treatment alternative compared to synthetic drugs and more accessible to the population. However, it is necessary that the use of phytotherapy is not restricted exclusively to popular knowledge, but based on scientific knowledge, thus contributing to the appropriate insertion of this practice in health care. The objective of this study was to evaluate the knowledge about medicinal plants and herbal medicines of hypertensive patients attended in a cardiology office in the city of Umuarama-PR. A quantitative and descriptive study was developed, applying a questionnaire, by Google Forms, to evaluate the knowledge on the subject, with all hypertensive patients attended in a cardiology office in August and September 2020. The results showed that 47% of patients know some medicinal plant with hypotensive effect, and the transmission of knowledge between generations is the main way of acquiring information. Of those who use some plant for this purpose, 60% perceived positive effects on tension levels, with low rates of side effects mentioned. Considering, on one hand, the high incidence of hypertension, the low rate of effective control of tension levels and low adherence to treatment and, on the other hand, the vast Brazilian biodiversity and the potential for the production of herbal medicines, the improvement in this area is very promising.